Sąd Najwyższy Gruzji – kilka uwag o jego organizacji, kognicji i siedzibie - Misztal-Konecka, Joanna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The Supreme Court of Georgia is a part of judicial power next to the Constitutional Court and common courts. Basing the principles of its functioning on the organic law on common courts of 4 December 2009, the Supreme Court is primarily concerned with actitives pertaining to cassation since it is the court of the highest and final instance of the justice system in Georgia. The article presents the principles regulating the appointment of judges of the Supreme Court, status of judges and Presidents of the Supreme Court, competencies of the Supreme Court, and its structure. The seat of the Supreme Court which is a work of the Polish architect Aleksander Szymkiewicz, is also described in detail.